Potential Water Requirement of Eucalyptus - A Preliminary Study - Singh, S. B.; Kumar, Pramod; Prasad, K. G. (Indian Forester, 1993)
Factorial experiment conducted under 5 mulch (control, rice husk, pine needles, hare droppings and farm yard manure) and 3 irrigation levels (equivalent to 100, 75 and 50% of evaporation) showed reduction in biomass production but an increment in potential water use of Eucalyptus with decrease in water level. Taking 100% water addition as standard, 25 and 50% reduction in water supply brought to 25 and 37% reduction in biomass but increased water use efficiency by 5 and 26%.